Glycation restrains open-closed conformation of Insulin. (February 2023) - Jeevanandam, Jayanth; Paramasivam, Esackimuthu; Saraswathi, N.T.
Abstract: In hyperglycemic conditions, the level of reactive dicarbonyl metabolites concentration is found to be high, which plays a significant role in protein glycation. Despite decades of research, the effect of methylglyoxal on the structure and function of insulin is still unknown. Through a shift in conformation at the B-chain C-terminal (BT-CT) hinge from an "open" to a "wide-open" conformation, insulin binds to the receptor and activates the signal cascade. Insulin resistance, which is the main sign of Type 2 Diabetes, can be caused by a lack of insulin signaling. Methylglyoxal site-specific glycation in residue R22 at B chain forms AGE product Methylglyoxal-hydroimidazolone (MGH1) in insulin. In this work, we present molecular dynamics study of this glycated insulin R22MGH1, which revealed new insights into the conformational and structural changes. We find the following key results: 1) B-chain in insulin undergoes a closed conformational change upon glycation. 2) Glycated insulin shows secondary structure alteration. 3) Glycated insulin retains its closed shape due to an unusually strong hydrophobic contact between B-chain residues. 4) Wide open native conformation of insulin allows the B chain helix to be surrounded by more water molecules compared to the closed conformation of glycated insulin. The closed conformation of glycated insulin impairs its binding to insulin receptor (IR). Graphical Abstract: ga1 Highlights: Glycation impacts the conformational changes in Insulin. Principal Component Analysis revealed that glycated insulin B-chain turns into a closed conformation. Closed conformation of glycated insulin impairs the ability to bind Insulin receptors.